Efektivitas Mata Pelajaran Pendidikan Agama Islam Terhadap Karakter Siswa Di Luwu Timur - Khaerunnisa Khaerunnisa; Hikmawati Usman; Muhammadong Muhammadong; Ahmad Rijali Fiqri (Departement of Mathematics Education, 2024)
This research is qualitative research which aims to determine the effectiveness of Islamic Religious Education subjects on the character of UPTD students at SDN 271 Apundi Towuti East Luwu. The research subjects were 26 VB class students. Data collection uses a questionnaire. The data analysis technique uses a survey method. The research results obtained are that the effectiveness of Islamic Religious Education subjects carried out by teachers has been effective. This can be seen from the way teachers organize learning time and the curriculum for Islamic Religious Education subjects, the material taught is relevant to everyday life, provides an understanding of the teachings and values ​​of the Islamic religion, respects the diversity of religions and beliefs so that it can involve interaction between teachers. and students actively, assessments and evaluations are carried out fairly. Apart from that, the program plan prepared by the teacher also takes into account the diversity of students without distinguishing between religious or cultural backgrounds and provides open materials that are interesting and varied so that they are easy to understand because they take into account the learning styles and individual needs of students. Therefore, student character emerges which is reflected in the learning process, such as discipline, responsibility, honesty, politeness and tolerance. With this PAI subject, it is easy to shape students' character, not only at school but also at home or in the community. Moreover, students' understanding and knowledge can be integrated well and have a positive impact on themselves, their friends and also the community they meet. So PAI learning is meaningful for those who really study and deepen the learning taught at school. We also hope that schools can provide activities with a religious theme so that they can show more enthusiasm for religion.